Metastatic Squamous Cell Carcinoma of the Anus to the Lung Confirmed with Allelotyping. (9th February 2014) - Roth, Rachel; Moffatt-Bruce, Susan; Leon, Marino E.
Abstract : Histopathologic techniques are insufficient for distinguishing primary squamous cell carcinoma (SCC) from metastatic SCC, which is clinically important. A patient with SCC of the anus was found to also have SCC of the lung, and the question of metastatic versus synchronous primary diseases was raised. Immunohistochemical and hematoxylin and eosin (H&E) staining on sections of tissue could not discriminate between the two entities. Immunostain for p16 and chromogenic in situ hybridization for human papillomavirus (HPV) type 16 were positive in both tumors. Additionally, allelotyping for loss of heterozygosity displayed similar findings and confirmed the histopathological impression of anal SCC metastasis to the lung. The patient was treated with palliative chemotherapy instead of additional surgical treatment. When multiple tumors are present, determining metastatic versus synchronous primary tumors is necessary for appropriate treatment. Identification can be achieved using allelotyping for loss of heterozygosity.